JURNAL PENGARUH GAMIFICATION DAN PERCEIVED ENJOYMENT TERHADAP REPURCHASE INTENTION PADA PEMBELIAN DI SHOPEE: PENGARUH GAMIFICATION DAN PERCEIVED ENJOYMENT TERHADAP REPURCHASE INTENTION PADA PEMBELIAN DI SHOPEE - AHMAD SHOFIUZZUHRI, AHMAD SHOFIUZZUHRI (EL- Hayah, 2022)
This research aims to determine the effect of Gamification and Perceived Enjoyment on Repurchase Intention. The type of research used is descriptive verification, namely by describing and explaining the variables studied and then drawing conclusions. The variables in this research are gamification and Perceived Enjoyment (X) repurchase intention (Y). This type of research is primary data, namely data obtained directly by researchers through questionnaires, with test results from student and female respondents who are in the UIN Raden Mas Said Surakarta area shopping at Shopee. The method that can be used in this research is to use variance-based Structural Equation Modeling (SEM) analysis, namely Partial Least Square (PLS). This research uses the smart PLS 4.0 computer program and determines variables that are significant to repurchase interest (Y). Based on the results of the research that has been carried out, the variables obtained by influencing repurchase intention (Y) are the gamification variable (X1) and the perception of intention variable (X2). Keywords: Gamification, Perceived Enjoyment, Repurchase Intention